Penafsiran Tentang Pendidikan Birr al-Walidayn dalam Surat Al-Isra’ Ayat 23-24 - Komaru Zaman; Rofi’atul Afifah; Rizki Dwi Oktavia (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2022)
Birr al walidayn education is one of the most important factors in ideal character education. The creation of a generation that has good character is a dream for parents to their children. Birr al walidayn education is very influential on adab to parents. In the Qur'an, Allah SWT. has explained many verses related to Birr al walidayn. Allah tells the story of a mother's struggle so that a child can know the struggle of a mother so that she can repay him by being kind to him and not being disobedient to him, even if one of them is not to say "ah" which has been explained in Surah al-Isra verse 23. verse 23, there are several prohibitions in the words of Uffin, prohibition of shouting with harsh words, saying with noble words. The Qur'an and the Sunnah emphasize Birr al walidayn as an obligation. The rights and obligations of respecting, obeying and doing good to both parents are not only because both of them are a factor in their existence or because both of them first did good deeds to them so that they are obliged to repay them equally, but because Allah Himself obliges them to obey them This explains how much Islamic concern for both parents.